2012
DOI: 10.1007/s00423-012-0911-2
|View full text |Cite
|
Sign up to set email alerts
|

HCC: current surgical treatment concepts

Abstract: The improvement of survival in HCC patients after surgical treatment results from refinements in surgical technique and better identification of adverse prognostic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 145 publications
1
35
0
1
Order By: Relevance
“…For long time, there had been a consensus that a diagnosis of Child-Pugh class C was a contraindication for [31]. Abdel-Atty et al [32] reported safe LLR in three Child-Pugh class C patients.…”
Section: Discussionmentioning
confidence: 99%
“…For long time, there had been a consensus that a diagnosis of Child-Pugh class C was a contraindication for [31]. Abdel-Atty et al [32] reported safe LLR in three Child-Pugh class C patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although liver transplantation is also a treatment option, the shortage of donated organs limits its wider application in clinical practice. Other therapeutic measures, including chemotherapy and transcatheter arterial chemoembolization have been used to treat HCC, but have failed to produce an observable effect (5). Therefore, increased knowledge concerning the underlying mechanisms of the tumorigenesis and/or progression of HCC is urgently required to identify an effective method for managing patients with HCC.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the microenvironment in HCC (see pages [14][15] has led to proposals that simple blood test estimates of inflammation are important patient prognosticators.…”
Section: Newer Hepatocellular Carcinoma Tumor Markers Proteomics CImentioning
confidence: 99%